Pelatihan Pemanfaatan Mendeley sebagai Reference Tool untuk Penulisan Ilmiah bagi Young Researcher - Muthia Anggraini; Virgo Trisep Haris; Alfian Saleh (Jurnal Pengabdian KOLABORATIF, 2024)
The use of reference management applications or citation managers such as Mendeley can help students who are working on their final assignments to write their theses more comprehensively. In the process of working on a final assignment, there are often limitations in accessing popular reference sources. A community service activity with our partner, Young Researchers in Pekanbaru City, this activity aims to assist our partners in making citations to facilitate the completion of their final reports. The solution offered by the service team is to provide training on using Mendeley. The implementation method used includes lectures, discussions, and evaluations through the provision of pre-tests and post-tests. The pre-test results showed that 82.26% of participants were unable to install the application, and after the training, the post-test results indicated that 100% of the participants were able to install, use the Mendeley application, and create a bibliography.